Pengaruh Modal, Tenaga Kerja dan Pengalaman Terhadap Produksi Pengolahan Ubur-Ubur di Desa Temajuk - Rivaldo; Saifullah; Januardy, Uray (Nekton, 2021)
The purpose of this study is to know the effect of capital, labor, and experience on jellyfish processing production in Temajuk Village. The method used is observation, interviews, and questionnaires with primary data and secondary data. The data that has been obtained is analyzed by the correlation test method using SPSS version 25. The results of the correlation test for the capital variable obtained Rcount 0,813 > Rtable 0,514, the results show that the variable of capital has an effect on the variable production results. For the labor variable, the Rcount is 0,793 > Rtable 0,514, this result shows that there labor variable has an effect on the variable of production results. For the experience variable obtained Rcount 0,273 < Rtable 0,514 the results show that the experience variable has no effect on the production yield variable.